Assessment of medication administration of nurses in medical cardiac wards and its relationship with some demographic characteristics: An observational study - Hajar Najafi; Sedigheh Farzi; Mohammad Javad Tarrahi; Sima Babaei (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Unsafe medication administration and medication errors pose a threat to medication safety. Safe medication is one of the most important nursing practices that plays an important role in preventing medication errors. The aim of this study was to assess the medication administration of nurses in cardiac wards and its relationship with some demographic characteristics. MATERIALS AND METHODS: The present study was conducted as an observational study in 2021 with the 60 nurses who working in the medical cardiac wards of one selected hospital affiliated with the Isfahan University of Medical Sciences. Data were collected using three-part tools (demographic information, medication checklist (55 items), and documentation checklist (8 items). The checklist was completed by the observer after observing the nurses' medication administration. Data analysis was conducted using descriptive and inferential statistics in the SPSS software (version 16, SPSS Inc., Chicago, IL, USA). A P < 0.05 was considered statistically significant. RESULTS: The mean total score of the principles of injection and oral medication administration were 82.53 ± 10.75 and 75.76 ± 9.62, respectively. The mean score of the principles of injection and oral medication administration in the morning shift was significantly higher than the evening and night shifts (P < 0.001). The relationship between the mean score of the principles of injection medication (r = 0.234, P = 0.067), oral medication (r = 0.222, P = 0.083), and the nurses' work experience no significant. The rate of adherence to the principles of medication administration in the premedication administration stage was higher than during and after drug administration. CONCLUSION: Although the mean score of medication administration of nurses in the medical cardiac wards was at the desired level, it is necessary to monitor and plan by nursing managers to improve medication administration. Reducing the number of night shifts, adhering to accreditation programs in the hospital, continuous monitoring of nurses in terms of compliance with the principles of medication are among the proposed solutions to improve the safe medication in nurses.